A historical approach to Child Health in Peru: Women and the caring of Childhood (1900-1930) - Emma Mannarelli, Maria (2011)
The policies on children´s health in Peru began as the Peruvian State assumed it function as the main actor of the health system. This implied not only public but also private actions, in which women contributions where of significant meaning. They dialogued and interacted with the medical and pedagogic scientific discourses regarding the importance of childcare, considered as a cornerstone of the progress of the nation